2000
DOI: 10.1212/wnl.54.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension

Abstract: This study supports previous reports that link obesity and psychosocial difficulties, but obesity alone is not the explanation for the higher levels of depression and lower levels of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 16 publications
7
69
0
Order By: Relevance
“…Two previous studies have shown IIH to be associated with poorer scores on SF-36 when compared with healthy controls [19,20]. With the possible exceptions of the subscales Pain and Change in Health, the values in this study appeared similar to normal scores from population studies.…”
Section: Protocol Compliancesupporting
confidence: 78%
“…Two previous studies have shown IIH to be associated with poorer scores on SF-36 when compared with healthy controls [19,20]. With the possible exceptions of the subscales Pain and Change in Health, the values in this study appeared similar to normal scores from population studies.…”
Section: Protocol Compliancesupporting
confidence: 78%
“…43 Patients with PTC also appear to have depression and anxiety to a greater extent than weight-matched controls and healthy controls. 44 Health-related quality-of-life scores are also affected in PTC, with patients reporting significantly lower general health than controls and patients with other neuro-ophthalmologic conditions. 31 Restoration of visual acuity and resolution of papilledema constitute the primary goals of management in PTC and the benchmark of relative success of a treatment technique.…”
mentioning
confidence: 99%
“…Interestingly, patients with idiopathic intracranial hypertension, a neurological disorder characterized by nontraumatic elevations in ICP, exhibited higher rates of developing depression and anxiety, as compared to matched control patients (Kleinschmidt, Digre, & Hanover, 2000). These clinical findings suggested post-traumatic elevations in ICP could directly induce psychiatric co-morbidities.…”
Section: Discussionmentioning
confidence: 96%